3D models of Quaternary-aged sedimentary successions within the Canterbury, New Zealand region. Issue 4 (2nd October 2017) - Lee, Robin L.; Bradley, Brendon A.; McGann, Christopher R.
ABSTRACT: A 3D high-resolution model of the Quaternary geological stratigraphic sequence in the Canterbury, New Zealand region is developed utilising datasets of over 500 high-quality water well logs from a database of 29, 985, and over 370 near-surface cone penetration test (CPT) records from a database of 13, 670. The model, developed using geostatistical Kriging, represents the complex interbedded regional Quaternary geology by characterising the boundaries between significant interbedded geological formations as 3D surfaces. The model is examined in the form of both geological surface contour maps and vertical cross sections, where the most evident trend identified is the easterly dip caused by the dominant alluvial deposition of terrestrial sediments. The developed 3D interbedded Quaternary stratigraphy model has several applications for hydrologic modelling, earthquake-induced ground motion simulations and seismic site characterisation. For the latter case, the role of the model in constraining surface wave analysis-based shear wave velocity profiling is illustrated.